Revealing the Meaning of Implementing the Tax Amnesty Program Through Phenomenology Approaches - Azizah, Zahrotul (Jurnal Dinamika Akuntansi, 2018)
The aim of this study is to explore the implementation of the tax amnesty program. This research was conducted on taxpayers, tax authorities, and tax consultants using the phenomenology approach. The type of data in this study is qualitative data, namely non-numeric data in the form of words that are able to describe information and phenomena. Qualitative data in the form of transcripts of the results of in-depth interviews arranged into a working paper and mapping table. The data validity procedure used in this study first triangulated the data source and returned the entire written narrative to the informants for examination. The informant consisted of 5 people consisting of taxpayers, tax authorities, and tax consultants in Malang City. The findings indicate that from the taxpayer’s side understanding, the tax amnesty program is as an opportunity to correct errors. From the side of the tax authorities understands, it is as a program that has not been carefully prepared based on various obstacles experienced by the tax authorities during the implementation of the program. The last, from the tax consultant’s side understanding, the tax amnesty program as a new beginning to raise tax awareness. The implication of this study is that the tax amnesty program as a fiscal policy has an impact on increasing taxpayer tax awareness but unfortunately this policy is not prepared properly so that the final results are still far from the set targets. This study can provide an evaluation of fiscal policies and improvements to the taxation system in the future so that it will have a positive impact on tax revenues.